Effect of newly refined hypocenter locations on the seismic activity recorded during the 2016 Kumamoto Earthquake sequence - Tomoko Elizabeth Yano (Earth, Planets and Space, 2017)
Abstract We present the results of relocating 17,544 hypocenters determined from data recorded during the 2016 Kumamoto Earthquake sequence, during the interval between April 14, 2016, and August 31, 2016. For this, we used a double-difference relocation method to constrain high-resolution hypocenter locations by cross-correlation differential times as well as the NIED Hi-net catalog differential times. The sequence included two large events (on 14 April: M JMA6.5 and on 16 April: M JMA7.3) that occurred in a complicated region where the Hinagu and Futagawa faults meet. By comparing these high-resolution earthquake locations in three different periods [(P1) between 2001 and 2012; (P2) between M JMA6.5 and M JMA7.3; and (P3) between M JMA7.3 and August 31, 2016], we present the significant seismicity after the mainshock relative to the background seismicity. Events during the Kumamoto Earthquake sequence occurred generally within the same sites of known faults and background seismicity. For an example, the seismicity during period P2 formed a sharp linear shape along the northern part of the Hinagu fault for about 20 km. A series of linear seismicity events occurred during period P3 along the Futagawa fault to the east (for about 28 km), in the northern part of the Aso caldera, and in the Oita region around the Beppu–Haneyama fault zone. These events also extended to the mid- and southern parts of the Hinagu fault zone and were shaped only after the M7.3 event. Moreover, high-resolution hypocenter locations also allowed us to identify some clusters of events that occurred in regions where background seismicity has not been confirmed. For instance, activity on the northwestern edge of the Aso caldera and in small areas within the Beppu–Haneyama fault zone became apparent with new seismic activity. We also demonstrate herein the absence of seismicity between the northeast extension of the Futagawa fault zone and the Aso caldera region, which became clearly shown after the M7.3 event. This low-seismicity region is located at the boundary of the low- and high-velocity structures and different focal mechanisms, but is also close to the maximum slip area of the M7.3 event.